(untitled) (Research, Society and Development, 2022)
Temporomandibular disorders (TMDs) are diseases that involve the temporomandibular joint, masticatory muscles and associated structures, with pain as one of its main symptoms and which may be associated with comorbidities. However, the association between TMDs and gastrointestinal disorders (GIDs) is still poorly studied. DGIs can be classified as organic when associated with an anatomic cause or tissue damage, and functional when no pathological findings are evident, in the absence of an anatomical cause or tissue damage. Therefore, this study seeks to investigate, through a literature review, the possible association between TMDs and DGIs of a structural or functional nature. This is a bibliographic search in the PubMed and SciELO databases in August 2022, without limitations in the search in terms of language and publication date. The descriptors used for the search were: “irritable bowel syndrome”; “gastroesophageal reflux disease”; “gastritis”; “Crohn’s disease”; “constipation” and “temporomandibular disorders”. A total of 53 articles were found and 18 of these were included. Based on the present review, it can be stated that there is a potential association between TMDs and specific DGIs, namely: irritable bowel syndrome, gastroesophageal reflux disease and gastritis/peptic ulcer. This association can be justified by possible comorbid mediating factors, namely: somatization, anxiety, depression, pain catastrophizing and sleep disorders.